Development of Ethno-Vlog Integrated E-Worksheet (E-LKPD) to Enhance Students’ Scientific Literacy in Biotechnology Learning - Yoseph Binsasi; Ani Rusilowati (Unnes Science Education Journal, 2026)
Scientific literacy is a crucial competency in the 21st century, enabling students to understand scientific concepts and apply them in real-life contexts. However, Indonesian students’ scientific literacy remains relatively low based on international assessments. This study aims to develop an Ethno-Vlog integrated Electronic Student Worksheet (E-LKPD) on biotechnology materials and evaluate its validity, practicality, and effectiveness in improving students’ scientific literacy. This research employed a Research and Development (R&D) approach using a modified 3D model (Define, Design, Develop). The participants were 47 twelfth-grade students from a senior high school in East Nusa Tenggara, Indonesia. Data were collected through expert validation sheets, student response questionnaires, and scientific literacy tests. The results indicate that the developed E-LKPD is highly valid (material expert = 81.25%; media expert = 89.71%), practical (student response = 82.72%), and moderately effective in improving scientific literacy (N-Gain = 0.63). The integration of ethnoscience and digital media enhances contextual learning and student engagement. Therefore, the developed E-LKPD is suitable for use in science learning to foster scientific literacy.